Comparison of diesel emission experiments in view of the environment: a case study at Dubai - Al Ali, Yousif; Hrairi, Meftah; Al Kattan, Ibrahim (World Academic Union, 2012)
Because of the nature of the diesel engine combustion process, such engines produce more toxic emissions, more visible smoke and odour than gasoline engines. This has led to an increasing concern about the possible effects of diesel emissions on the environment and human health. This study examines emissions form two experimental diesel powered vehicles pilot schemes at a Dubai municipality; an inspection and maintenance experiment and a diesel particulate filter experiment. Comparing the two experiments with a baseline vehicle, the results indicate that after the inspection and maintenance experiment, a significant reduction in emissions was achieved in carbon monoxide (300%), nitrogen oxides (500%) and hydrocarbons (88%). The implementation of a diesel particulate filter lead to even better emission reductions but at a higher cost, with hydrocarbon emissions decreasing by 150%, carbon monoxide by 500% and nitrogen oxides by 700%. The results are promising for both experiments for future investigation.